2020
DOI: 10.1177/0269215520971795
|View full text |Cite
|
Sign up to set email alerts
|

Stationary cycling exercise for knee osteoarthritis: A systematic review and meta-analysis

Abstract: Objective: To evaluate effects of stationary cycling exercise on pain, function and stiffness in individuals with knee osteoarthritis. Data sources: Systematic search conducted in seven databases (PubMed, Embase, Cochrane Library, Web of Science, EBSCO, PEDro, and CNKI) from inception to September 2020. Review methods: Included studies were randomized-controlled trials involving stationary cycling exercise conducted on individuals with knee osteoarthritis. End-trial weighted mean difference (WMD) and 95% confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Inclusion criteria were as follows: (1) patients met the diagnostic criteria of osteoarthritis of the knee [ 4 ]; (2) patients met the syndromes of the Clinical Research Guidelines for New Chinese Medicines for Osteoarthrosis [ 5 ]; (3) morning stiffness of 30 min and less and frictional sounds when the joint was present; (4) X-ray showed joint space narrowing in weight-bearing position; and (5) informed and agreed to this study.…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria were as follows: (1) patients met the diagnostic criteria of osteoarthritis of the knee [ 4 ]; (2) patients met the syndromes of the Clinical Research Guidelines for New Chinese Medicines for Osteoarthrosis [ 5 ]; (3) morning stiffness of 30 min and less and frictional sounds when the joint was present; (4) X-ray showed joint space narrowing in weight-bearing position; and (5) informed and agreed to this study.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, results here showed that gains on the stiffness sub-scale of the WOMAC were less than its relevant MCID value, despite being statistically significant. There are two possible explanations for this finding: (1) individuals treated with high intensity laser are always in a static state ( 37 ), while the improvement of stiffness typically requires range of motion training that involves repeated flexion and extension of the knee joint ( 44 , 49 , 50 ). Consequently, HILT does not bring about changes that promotes utilization of knee range of motion ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…These exercises were selected in order to capture straight-leg movements in both the sagittal (SLA) and frontal (SLF) planes, and knee flexion with (SLS) and without load (KL), thus facilitating the validation of the technique in different conditions and when different numbers of AE events are produced. Moreover, such exercises are frequently utilized in rehabilitation programmes in cases of post-injury, knee replacement, and osteoarthritis [ 29 , 30 , 31 ]. Knowing which exercises produce valid AE measures has the potential to improve not only AE diagnostic value, but also rehabilitation programmes by using AE to evaluate the patient’s progression in a more objective manner.…”
Section: Methodsmentioning
confidence: 99%